Autoimmune encephalitis: A costly condition. (26th February 2019) - Cohen, Jesse; Sotoca, Javier; Gandhi, Shikha; Yeshokumar, Anusha K.; Gordon-Lipkin, Eliza; Geocadin, Romergyko G.; Frick, Kevin D.; Probasco, John C.; Venkatesan, Arun
Abstract : Objective: To assess the inpatient hospitalization burden and costs of patients with autoimmune encephalitis (AE) at a tertiary care institution. Methods: Adult inpatients with AE were identified retrospectively from July 1, 2005, to June 30, 2015. Demographic and clinical data were collected and analyzed. Billing data were compared to those of patients with herpes simplex encephalitis (HSE). Charges were adjusted for inflation. Results: Of 244 admissions for encephalitis reviewed, 63 patients met criteria for probable or definite AE. Thirty-one (49%) patients were antibody positive, and 27 (43%) were admitted to the intensive care unit (ICU). Median hospital charges per patient with AE were more than 70, 000; median length of stay (LOS) was 15 days; and in-hospital mortality was 6%. Patients admitted to the ICU had substantially higher median hospital charges (ICU 173, 000 per admission vs non-ICU 50, 000 per admission, p < 0.001). LOS was strongly associated with charges and was driven by delay in diagnosis of AE, prolonged treatment courses, and lack of response to therapy. Compared with HSE, median hospital charges per patient with AE were nearly 4 times higher, median AE LOS was 3 times higher, and total charges over the study period were nearly twice as high. Conclusions: Patients with AE used more inpatient health care resources per patient during a 10-year period than patients with HSE at our institution. ICU-admitted patients with AE were responsible for a substantially higher financial burden than non–ICU-admitted patients with AE. Our data underscore the need for the development of novel diagnostic and therapeutic modalities to improve patient outcomes and to decrease hospital burden in AE.